The Study of pH and Ionic Strength on Ni(II) and Pb(II) sorption using Humic Acid-Urea Formaldehyde (AHUF) - Meidita Kemala Sari; Bambang Rusdiarso (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
The study of pH and ionic strength on Pb(II) and Ni(II) sorption with AHUF adsorbent has been investigated. The AHUF was synthesized from humic acid (AH) with urea-formaldehyde (UF) and characterization by FTIR, SEM-EDX, total acidity content, and pH zero point charge (pHpzc). The study of pH and ionic strength using the batch system. The formation of AHUF was identified based on; decreases in total acidity (349.30 cmol/kg), emerging peaks at 3351, 1258, and 1049 cm-1 by FTIR, and increases of N atoms 21.06% by EDX. The results indicate the adsorption of Pb(II) and Ni(II) are strongly dependent on pH and ionic strength at pH < 6. The AHUF have a pHpzc value is 4.82 with optimum sorption on pH 5. The variations of NaCl to adsorption Pb(II) and Ni(II) caused a decrease in the value of ionic activity from 0.999 M – 0.309 M, the amount of adsorbed will decreased.